Minority statuses and mental health outcomes among young gay, bisexual and queer men in Singapore. Issue 1 (2nd January 2023) - Tan, Rayner Kay Jin; Yang, Daryl W. J.; Le, Daniel; Tan, Avin; Tyler, Adrian; Tan, Calvin; Kwok, Chronos; Banerjee, Sumita; Wong, Mee Lian
Abstract: Minority gay, bisexual and queer (GBQ) men face not only stigma from the general population based on their sexual orientation, but stigma as well based on their race, body type and their gender identity. Results of this study were derived from baseline data of the Pink Carpet Y Cohort Study in Singapore comprising a sample of 570 GBQ men aged 18 to 25 years old. Controlling for key demographic variables, being non-Chinese was associated with depression severity (aPR = 1.21, 95%CI [1.01, 1.45]), experienced homophobia (aPR = 1.13, 95%CI [1.05, 1.22]) and a past suicide attempt (aPR = 1.77, 95%CI [1.08, 2.92]); being non-cisgender male was associated with depression severity (aPR = 1.27, 95%CI [1.05, 1.55]) and experienced homophobia (aPR = 1.20, 95%CI [1.09, 1.32]); reporting a BMI of 25 or more was associated with depression severity (aPR = 1.20, 95%CI [1.00, 1.44]). Reporting one minority status was associated with depression severity (aPR = 1.23, 95%CI [1.05, 1.45]) experienced homophobia (aPR = 1.08, 95%CI [1.01, 1.15]), and a past suicide attempt (aPR = 1.61, 95%CI [1.01, 2.56]), while reporting at least two minority statuses was associated with depression severity (aPR = 1.47, 95%CI [1.17, 1.83]), experienced homophobia (aPR = 1.26, 95%CI [1.14, 1.40]), and past suicide ideation (aPR = 1.28, 95%CI [1.01, 1.62]), compared to participants in the general sample. Interventions are needed to buffer the effects of stigma in this vulnerable group of individuals. Supplemental data for this article is available online at https://doi.org/10.1080/19361653.2021.1940414 .